2022
DOI: 10.1038/s41746-022-00719-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cardio-respiratory fitness prediction through wearables in free-living environments

Abstract: Cardiorespiratory fitness is an established predictor of metabolic disease and mortality. Fitness is directly measured as maximal oxygen consumption (VO2max), or indirectly assessed using heart rate responses to standard exercise tests. However, such testing is costly and burdensome because it requires specialized equipment such as treadmills and oxygen masks, limiting its utility. Modern wearables capture dynamic real-world data which could improve fitness prediction. In this work, we design algorithms and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Data generated from a combination of mobile devices and WS that had a common platform (Apple Health; Achievement) extracted similar variables [ 87 , 88 ]. Particularly amongst large-scale research with many participants, these pre-calculated features were utilised for analysis rather than raw data [ 88 , 89 ]. Some research reported utilising pedometers as their WS to collect patient data; these pedometers all included accelerometers rather than a traditional step counter allowing them to represent the intensity of movement [ 90 ].…”
Section: Hardware/sensing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data generated from a combination of mobile devices and WS that had a common platform (Apple Health; Achievement) extracted similar variables [ 87 , 88 ]. Particularly amongst large-scale research with many participants, these pre-calculated features were utilised for analysis rather than raw data [ 88 , 89 ]. Some research reported utilising pedometers as their WS to collect patient data; these pedometers all included accelerometers rather than a traditional step counter allowing them to represent the intensity of movement [ 90 ].…”
Section: Hardware/sensing Technologiesmentioning
confidence: 99%
“…One large cohort study used the Actiheart wearable ECG, which places two leads on the sternum from which three papers analysed the HR data [ 66 , 89 , 114 ]. Other research utilised an ECG ‘necklace’, which involved placing electrodes in the II lead configuration on the chest (see Figure 6 c) whilst a further project included an ECG sensor that was integrated into a smart shirt (Hexoskin), see Figure 6 b [ 115 , 116 ].…”
Section: Hardware/sensing Technologiesmentioning
confidence: 99%
“…In healthy individuals, HR responses to activity are defined by an increase in HR that is concurrent to the increasing intensity of the activity [134]. More recently, the Apple Watch has introduced cardio-respiratory fitness (CRF) features [135] while large population-scale studies showed that these HR responses can predict VO 2 max [136].…”
Section: Ai For Mobile Health—case Studiesmentioning
confidence: 99%
“…Wearable devices, such as activity trackers and smartwatches, increasingly provide opportunities for non-intrusive objective monitoring of biological signals such as HR and movement during free-living, potentially enabling more precise prediction of VO 2 max without the need to conduct a specific exercise test [140]. A recent large-scale analysis used data from Fenland Study ( N = 11 059), along with its longitudinal cohort ( N = 2675), and a third external cohort using the UK Biobank Validation Study ( N = 181) who underwent maximal VO 2 max testing, to show that the combination of wearables and other biomarkers as inputs to neural networks yields a strong correlation to ground truth in a holdout sample ( r = 0.82, 95normal% CI: 0.800.83) [136]. It also detects fitness change over time (e.g.…”
Section: Ai For Mobile Health—case Studiesmentioning
confidence: 99%
See 1 more Smart Citation